HUBUNGAN PENGGUNAAN TAS PUNGGUNG DENGAN KELUHAN MUSKULOSKELETAL PADA SISWA MI NASHRUL FAJAR METESEH KECAMATAN TEMBALANG KOTA SEMARANG - Lisanti Lisanti; Martini Martini; Baju Widjasena (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Carrying heavy school bags and the incorrectly false way of carrying them can be a risk factor for musculoskeletal complaints and spinal deformities. The prevalence of musculoskeletal complaints in children is increasing every year. This research aims to knowing related intake calcium and using of backpack with musculoskeletal complaints in elementary school childreen Nashrul Fajar Meteseh, Tembalang, of Semarang. The type of this research is analitic observational with the design research is cross sectional. The sample was elementary school student Nashrul Fajar Meteseh age 9-12 years, which was 115 respondents. The sampling technique was Total sampling. Bivariate analysis using chi square.The results showed the proportion of musculoskeletal complaints was 50,4%.There is a related between heavy bag(p= 0,004,OR=3,285) and carrying bag (p=0,006, OR=3,255) with musculoskeletal complaint. There is no related age(p= 0,573), sex (p= 0,513), IMT (p= 0,610) and duration of carrying bag (p= 0,413).Need to do socialization related to the use of a safe bag, provided a locker in the class so as not to carry bags too heavy. In addition, the role of parents to manage the bag material brought to school and the type of bag used.